Benefits of Goods & Services Tax and Its Impact on Taxpayers’ Satisfaction - Vaid, Yashwant Kumar; Singh, Vikram; Sethi, Monika (Indian Journal of Finance, 2020)
Indirect tax is imposed by the government on supply of goods and services. In India, the indirect tax regime has been through major modifications and every taxation system implemented had its benefits over its predecessors. The recent indirect tax regime, that is, Goods and Services Tax (GST) is considered as a major reform in indirect taxation. Implementation of GST considerably improved the taxation system in many regards compared to its predecessors. Taking a note of this, the current study was conducted with an aim to empirically identify the benefits of GST, as perceived by taxpayers, not only in theory, but practically as well, and recognize the impact of these benefits on taxpayers’ satisfaction. Data were collected from respondents of Raipur city with the help of a questionnaire. Factor analysis and path analysis were employed for the purpose of the study. The major benefits identified were Elimination of Multiple Taxes, Lesser Tax Evasion, and Satisfaction & Convenience. Path analysis was used to identify the impact of these benefits, where Satisfaction & Convenience was treated as a dependent variable and Elimination of Multiple Taxes and Lesser Tax Evasion were considered as independent variables. Based on the results and findings, it was concluded that Elimination of Multiple Taxes and Lesser Tax Evasion had a significant impact on satisfaction. This paper helped identify the areas where the taxpayers were satisfied with the implementation of GST and felt benefited because of it.